أهمية شركات التأمين التكافلي في حماية المصارف الإسلامية من التعثر المصرفي - طاري, عبد القادر; تومي, ابراهيم (جامعة الوادي University of Eloued, 2021)
ا شك أن نشاط المصارف الإسلامية يتعرض إلى العديد من المخاطر المصرفية، الأمر الذي يتطلب منها إتخاذ الأساليب والتدابير اللازمة والمتوافقة مع الشريعة الإسلامية،والتي يمكن من خلالها الحفاظ على سلامة واستقرار الجهاز المصرفي الإسلامي. وعليه تسعى هذه الدراسة إلى التعرف على أهم المخاطر التي تواجه المصارف الإسلامية والمتمثلة في المخاطر الإئتمانية،و إبراز دور نظام التأمين التكافلي كأسلوب حديث في تقوية و تعزيز إدارة هذه المخاطر للحد من هذه التعثرات التي تأثر على نشاط ومسيرة عمل المصارف الإسلامية، حيث بينت الدراسة أن التأمين التكافلي له دور في تخفيف وإدارة المخاطر الائتمانية وهذا استنادا على تجربة بنك البركة اللبناني،والذي استطاع أن يخفف مخاطره الإئتمانية باعتماد أسلوب التأمين التكافلي البديل الشرعي للتأمين التقليدي بتحويل المخاطر الإئتمانية من المصرف إلى شركة الأمان للتأمين التكافلي. There is no doubt that the activity of Islamic banks is exposed to many banking risks , Which requires it to take the necessary methods and measures that are compatible with Islamic Sharia, Through which it is possible to maintain the integrity and stability of the Islamic banking system, Accordingly, this study seeks to identify the most important risks facing Islamic banks, which are credit risks, And highlighting the role of the Takaful insurance system as a modern method in strengthening and enhancing the management of these risks to reduce these failures that affect the activity and work progress of Islamic banks,Where the study showed that Takaful insurance has a role in mitigating and managing credit risks, and this is based on the experience of the Lebanese Al Baraka Bank, And who was able to mitigate his credit risks by adopting the Takaful insurance method, a legitimate alternative to traditional insurance, by transferring credit risks from the bank to Al-Aman Takaful Insurance Company.
The importance of Takaful insurance companies in protecting Islamic banks from bank default (Al-Aman Takaful Insurance Company and Al-Baraka Lebanese Bank as a model)
مقال
Keywords: تأمين تكافلي ; تعثر مصرفي ; إدارة المخاطر ; بنك إسلامي